Community income of honey bee cultivation in protected forest edge area - Suarta, Gede; Kayana, I Gusti Ngurah; Dananjaya, I Gusti Agung Nyoman (International research journal of management, IT and social sciences, 2021)
This study aims to analyze the level of income, the minimum scale of the amount of honey beekeeping, and the minimum selling price for the honey produced so that farmers get profits. Determination of the location of the study using the purposive method with the consideration that Pempatan Village, Rendang District, Karangasem Regency is one of the honey centers. The population in this study amounted to 63 people who cultivate honey bees. Sampling in this study using purposive sampling method with the number of respondents as many as 30 people. The types of data needed in this study are primary data and secondary data. Primary data was obtained by conducting observations and interviews with respondents. The data analysis methods used in this study are (1) Revenue Analysis, (2) Revenue Cost Ratio, (3) Break Event point. Based on the research results, the community’s income from honey bee cultivation is IDR. 3.369.300,-/month while the R/C ratio of honey bee cultivation in Pempatan Village is 2.1, which means it is feasible to cultivate. If it is seen from the BEP Production from beekeeping is 7.08 liters, BEP Prices from honey bee cultivation are IDR. 154,516,-/liter and BEP Revenue from beekeeping is IDR. 2,337,145.